Extracorporeal photopheresis vs standard therapies for steroid‐refractory chronic graft‐vs‐host disease: Pharmacoeconomic assessment of hospital resource use in Spain. Issue 4 (8th May 2021) - Boluda, Blanca; Solana‐Altabella, Antonio; Cano, Isabel; Acuña‐Cruz, Evelyn; Rodríguez‐Veiga, Rebeca; Ballesta‐López, Octavio; Megías‐Vericat, Juan Eduardo; Martínez‐Cuadrón, David; Gómez, Ines; Solves, Pilar; Lorenzo, Ignacio; Piñana, Jose Luis; et al.
Abstract: Background: This study assessed pharmacoeconomic costs associated with extracorporeal photopheresis (ECP) compared with other available second‐line therapies for chronic graft‐vs‐host disease (cGvHD) in a tertiary Spanish institution. Methods: Patients (≥18 years) diagnosed with steroid‐refractory cGvHD were eligible. Data were collected retrospectively from index date until 1 year or relapse. Patients were distributed in two cohorts (ECP vs non‐ECP), matched by age (≤ or > 40), hematopoietic stem cell transplant (HLA‐identical sibling donor or other) and number of previous immunosuppressive lines (1, 2, or ≥ 3). Costs were assigned using the 2016 diagnosis‐related group (DRG) system: DRG 579 (€22 383) overnight stay due to major complication (ie, sepsis, pneumonia, parenteral nutrition, or respiratory failure), and DRG 875 (€5154) if no major complication. The primary endpoint was healthcare resource utilization per patient. Results: Forty patients (n = 20 per cohort) were included. Median age was 49, and 37.5% were female. Mean total cost per patient was €25 319 (95% CI: €17 049–€33 590) across the two cohorts, with a slightly lower mean cost per ECP‐treated patient (€23 120) compared with the non‐ECP cohort (€27 519; P = .597). Twenty‐seven inpatient hospitalizations occurred among ECP‐treated patients, vs 33 in the non‐ECP cohort. Day hospital and external consultations were more frequent in the ECP cohort. However, fewer inpatient admissions included DRG 579 compared with the non‐ECP cohort (44% vs 58%). Inpatient length of stay was slightly shorter in the ECP cohort (30 vs 49 days; P = .298). Conclusions: ECP treatment may yield economic savings in Spain through resource savings and moving costs toward outpatient care.